Acetate-induced apoptosis in colorectal carcinoma cells involves lysosomal membrane permeabilization and cathepsin D release - Marques, Carolina (2013)
Colorectal carcinoma (CRC) is one of the most common causes of cancer-related mortality. Short-chain fatty acids secreted by dietary propionibacteria from the intestine, such as acetate, induce apoptosis in CRC cells and may therefore be relevant in CRC prevention and therapy. We previously reported that acetic acid-induced apoptosis in Saccharomyces cerevisiae cells involves partial vacuole permeabilization and release of Pep4p, the yeast cathepsin D (CatD), which has a protective role in this process. In cancer cells, lysosomes have emerged as key players in apoptosis through selective lysosomal membrane permeabilization (LMP) and release of cathepsins. However, the role of CatD in CRC survival is controversial and has not been assessed in response to acetate. We aimed to ascertain whether LMP and CatD are involved in acetate-induced apoptosis in CRC cells. We showed that acetate per se inhibits proliferation and induces apoptosis. More importantly, we uncovered that acetate triggers LMP and CatD release to the cytosol. Pepstatin A (a CatD inhibitor) but not E64d (a cathepsin B and L inhibitor) increased acetateinduced apoptosis of CRC cells, suggesting that CatD has a protective role in this process. Our data indicate that acetate induces LMP and subsequent release of CatD in CRC cells undergoing apoptosis, and suggest exploiting novel strategies using acetate as a prevention/therapeutic agent in CRC, through simultaneous treatment with CatD inhibitors.